STRATEGI GURU MENGATASI KESULITAN BELAJAR IPAS SISWA KELAS IV SDN 33 BANYUASIN III - Rahmadona, Ocha; Idris, Muhamad; Irawan, David Budi (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to identify and analyze the strategies implemented by teachers in overcoming the learning difficulties of Natural and Social Sciences (IPAS) subjects in grade IV students at SDN 33 Banyuasin III. This study uses a descriptive qualitative approach with a saturated research method, where grade IV teachers are the subjects and grade IV students are the respondents. The instruments used in data collection include interview guidelines, observation sheets, and documentation. The research procedure is carried out through the stages of planning, implementing data collection, data analysis, and compiling reports. The results of this study indicate that students' learning difficulties include a lack of understanding of concepts, as well as limitations in using learning media. To overcome this, teachers apply strategies such as the use of interactive media, project-based learning approaches, providing individual guidance, and strengthening motivation in learning. These strategies are able to increase student participation and understanding in the IPAS learning process